Molecular identification and expression profiling of a novel alpha2-macroglobulin gene in giant freshwater prawn (Macrobrachium rosenbergii, De Man) - Likittrakulwong, Wirot; Na-Nakorn, Uthairat; Poompuang, Supawadee; Koonawootrittriron, Skorn; Srisapoome, Prapansak (Agriculture and Natural Resources, 2017)
A full-length cDNA encoding a novel alpha-2 macroglobulin (Mr-2α2M) gene in giant freshwater prawn was cloned and sequenced using rapid amplification cDNA end techniques. The Mr-2α2M was 5194 bp and comprised a 4560-bp open reading frame (ORF) encoding 1519 amino acid residues. The mature Mr-2a2M protein had a calculated molecular mass of 168.8 kDa and an estimated pI of 5.14. Mr-2a2M contained significantly functional domains, including a bait region, a thiol ester motif and a receptorbinding domain, similar to the a2Ms of other species. Amino acid sequence analysis of a2Ms indicated that Mr-2a2M was most similar to the Chinese white shrimp (Fenneropenaeus chinensis) a2M isoform 2 (Fc-A2M-2), with an identity of 58.8%, and the previously identified giant freshwater prawn Mr-1a2M protein, with an identity of 43.5%. Phylogenetic analysis revealed that Mr-2a2M was more closely related to Fc-A2M-2 than Mr-1a2M, which was placed in a different subminor group. Quantitative real-time reverse-transcription polymerase chain reaction assay illustrated that Mr-2a2M mRNA transcripts were strongly detected in the subcuticular epithelium, heart, midgut and muscle but marginally detected in the hemocytes of normal prawns. Immune response analysis in prawns stimulated with Aeromonas hydrophila clearly indicated that Mr-2a2M was quickly up-regulated to high levels in hemocytes and hepatopancreas after 12 h, in contrast to the expression pattern of Mr-1a2M. This novel a2M gene may have unique, important roles in giant freshwater prawn immune systems that differ significantly from those of the previously identified Mr-1a2M gene.